Gamma-radiation exposure-induced modifications in the thermal, dielectric, and electro-optical properties of two-room temperature antiferroelectric liquid crystal mixtures. Issue 15 (8th December 2022) - Debnath, Asim; Singha, Biplab Kumar; Goswami, Debarghya; Haldar, Sripada; Mandal, Pradip Kumar
ABSTRACT: The influence of different doses of gamma radiation on the phase transition temperatures, permittivity, conductivity, tilt angle, anchoring energy coefficients, spontaneous polarisation, rotational viscosity, and switching time of two-room temperature antiferroelectric liquid crystal (AFLC) mixtures has been investigated. At low radiation exposure, phase transition temperatures and optical tilt angles of the systems decrease slightly, but the effect is significant at high radiation doses. The permittivities as well as the ac and dc conductivities of the mixtures were significantly altered by γ-irradiation. Anchoring energy coefficients, spontaneous polarisation, rotational viscosity and switching time of the mixtures are shown to have a similar type of behaviour in both mixtures at low radiation doses, but their behaviour becomes random at higher levels of γ-irradiation. GRAPHICAL ABSTRACT: uf0001